Improvements of virulence factor phenotypic tests for Aeromonas salmonicida subsp. salmonicida, a major fish pathogen. Issue 1 (8th November 2021) - Girard, Sarah B.; Paquet, Valérie E.; Charette, Steve J.
Abstract: Aeromonas salmonicida subspecies salmonicida, a fish pathogen, expresses various virulence factors such as an A‐layer, lipases and proteases during the infection process. Not all strains of this bacterium express the same virulence factors. It is important to be able to evaluate which factors are present when characterizing strains. The A‐layer and secreted lipases and proteases are usually detected by agar‐based tests that require long incubation (24 h and more) and may provide ambiguous results. In the present study, protocols have been optimized to determine the presence of these virulence factors using liquid tests. For A‐layer detection, the optimized method stains the positive bacteria with Coomassie Brilliant Blue. The lipases are detected by a colorimetric biochemical reaction triggered by the degradation of p‐nitrophenyl dodecanoate into a yellow product detectable by spectrophotometry, if the result is positive. Both of these tests show results in less than an hour. Finally, the protease activity is measured by clarification of a medium containing milk during an overnight bacterial growth. These new protocols provide opportunities for quicker characterization of A. salmonicida subsp. salmonicida strains and, particularly, provide more precise results.